Predicting disease severity and remission in juvenile idiopathic arthritis: are we getting closer?. Issue 5 (September 2019) - Guzman, Jaime; Oen, Kiem; Loughin, Thomas
Abstract : Purpose of review: To summarize current research on the prediction of severe disease or remission in children with juvenile arthritis, and define further steps needed towards developing prediction tools with sufficient accuracy for clinical use. Recent findings: High disease activity, poor patient-reported outcomes, ankle or wrist involvement, and a longer time from onset to the start of treatment herald a severe disease course and a low chance of remission. Other studies confirmed that age less than 7 years and positive ANA are the strongest predictors of uveitis development. Preliminary evidence suggests ultrasound findings may predict flare in patients with clinically inactive disease, and several new biomarkers show promise. A few prediction tools that combine predictors to estimate the chance of remission or a severe disease course in the medium-term to long-term have shown good accuracy when internally validated in the population in which they were developed. Summary: Promising candidate tools for predicting disease severity and long-term remission in juvenile arthritis are now available. These tools need external validation in other populations, and ideally formal trials to assess whether their use in practice improves patient outcomes. We are definitively getting closer, but we are not there yet.